OPERATING SYSTEMS FOR ECONOMY AND MANAGERS - LAVRINCIK, Jan (Trends in education, 2011)
The article deals with the use of operating systems in the economic and managerial practise. It emphasized the positive and a weakness of individual systems, at the end of defines recommendations for practise.
Keywords: operating system; Windows; Mac OS X; iOS; Google Chromium OS.